Antimicrobial and prebiotic activities of tibia (Ficus nota) ethanolic leaf extract on selected intestinal microorganisms - Gasco, Marla M. Magtoto, Mariah Althea M. Marabulas, Trisha Mae M. Secreto, Vanessa Iriz B. Torres, Marco Emmanuel L. 4 0 16; 5
ABSTRACT: Ficus nota, commonly known as Tibig, is an endemic plant in the Philippines, traditionally utilized as an ethnomedicinal plant. Studies reported that its leaves possess secondary metabolites such as alkaloids, anthraquinones, flavonoids, saponins, and phenolic and flavonoid contents that are known to exhibit antimicrobial and prebiotic activities toward microorganisms. In this study, varying concentrations of the Tibig ethanolic leaf extract (TELE) were tested for its antimicrobial potential on three pathogenic microbes (Staphylococcus aureus, Escherichia coli, and Candida parapsilosis) and for its prebiotic potential on three probiotics (Lactobacillus plantarum, Bacillus subtilis, and Saccharomyces cerevisiae) thriving in the intestines. Prior to the actual experiments, brine shrimp lethality assay was conducted to determine the LC50 as the basis for the test concentrations used in this study. Broth microdilution method was conducted on the microorganisms, which was used to determine the extract's minimum inhibitory concentration (MIC). The study also used disk diffusion assay on intestinal pathogens. Based on the results of the study, all pathogenic microorganisms exhibited no zones of inhibition, while the MIC was not obtained. The prebiotic activities of TELE were examined through broth macrodilution and plate counting methods. All probiotic microorganisms reacted positively to the extract, as the colonies on most plates were too many to count (TMTC). The results show that Tibig ethanolic leaf extract is a prebiotic treatment for good bacteria rather than an antimicrobial agent for pathogenic microbes. This could be because of the presence of secondary metabolites, particularly flavonoids, glycosides, and tannins which have been reported to promote microbial growth. Keywords: antimicrobial, prebiotic, Ficus nota
Undergraduate Thesis: (BS in Medical Microbiology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2